Repetitive Myocardial Infarctions Secondary to Delirium Tremens - David Schwartzberg; Adam Shiroff (Case Reports in Critical Care)
Delirium tremens develops in a minority of patients undergoing acute alcohol withdrawal; however, that minority is vulnerable to significant morbidity and mortality. Historically, benzodiazepines are given intravenously to control withdrawal symptoms, although occasionally a more substantial medication is needed to prevent the devastating effects of delirium tremens, that is, propofol. We report a trauma patient who required propofol sedation for delirium tremens that was refractory to benzodiazepine treatment. Extubed prematurely, he suffered a non-ST segment myocardial infarction followed by an ST segment myocardial infarction requiring multiple interventions by cardiology. We hypothesize that his myocardial ischemia was secondary to an increased myocardial oxygen demand that occurred during his stress-induced catecholamine surge during the time he was undertreated for delirium tremens. This advocates for the use of propofol for refractory benzodiazepine treatment of delirium tremens and adds to the literature on the instability patients experience during withdrawal.